Technology, Employment and Wages - Addison, John T. (2001)
This paper examines the contribution of technological change to changes in the structure of relative employment and wages. Even if the nature of demand-side forces is fairly clear – international trade being of secondary importance because of the modest size of the between-industry employment shifts – the identification of the fundamental causes of skill-biased technological change, the techniques involved, and the manner of their adoption by firms is not transparent. Accordingly the skill-biased technological change diagnosis offers no real blueprint for policy other than the need for an increasingly better-educated labor force. The problems arise when one turns to the here-and-now, that is, the position of the currently skill-disadvantaged. Unfortunately, general solutions, although favored by politicians, are not available. Rather, there seems to be scope for carefully targeted programs that offer successive incremental improvements in the labor market prospects of truly disadvantaged workers whose education, skills and training are a significant impediment to their employment.